The Feasibility of Photovoltaic and Grid-Hybrid Power Plant for Water Pumping Station in Tabriz-Iran - Shirinabadi, Mohamadreza; Azami, Ahadollah (IEEE, 2018)
Energy supply to a regional grid for water pumping systems is sometimes difficult. But utilization of solar energy systems may meet energy requirements for such pumping systems. A pumping station covering an area of 16290 m(2) is studied in this research. The station is located in Tabriz city, Iran which has an annual solar insolation of 1884 kWh/m(2). The energy need for the pumping station is planned to be provided by an 800 kW photovoltaic (PV) power plant which uses one-axis sun tracker to increase the energy generation. The simulations are carried out using both PVSYST and HOMER software. The proposed PV power plant design has a performance ratio of 83.7%, and the electrical losses and geographic location of the designed area are considered along with the hardware equipment and environmental profits. Simulation results demonstrate that the land and climatic conditions -as the main factors- are strongly suggestible for the implementation and construction of the aforementioned PV power plant that reduces system losses while around 20% emission reduction for SO2, NOX, and CO2 can be achieved.
International Conference on Photovoltaic Technologies (PVCon) -- JUL 04-06, 2018 -- Middle E Tech Univ, Culture & Convent Ctr, Ankara, TURKEY
Keywords: PV power plant; hybrid; water pump; environmental benefits